Study of Chemical Composition of Essential Oil of Afsantine (Artemisia absinthium) and Inhibitory Effects of the Essential Oil and Its Aqueous and Alcoholic Extracts on some Food Borne Bacterial Pathogens - H Gandomi Nasrabadi; S Abbaszadeh; N Tayyar Hashtjin; I Yamrali (Institue of Medicinal Plants, ACECR, 2012)
Background: Increasing human knowledge about adverse effects of chemical preservatives has increased public interest to consume products with natural preservatives such as plant extract and their essential oils. Objective: In this study chemical composition of essential oil of Afsantine and antibacterial effect of its essential oil and aqueous, ethanolic and methanolic extracts against the most important food borne pathogens, salmonella typhimurium, Listeria monocytogenes, E. coli O157:H7, Bacillus cereus and Staphylococcus aureus were evaluated. Methods: Gas Chromatography-Mass Spectrometry (GC-MS) method was used for chemical composition analysis of the essential oil. Disk diffusion method was done to screen bacterial sensitivity. The Minimum Inhibitory Concentrations (MIC) of extracts were evaluated by broth micro-dilution method. Results: The essential oil components were identified and the major constituents of the oil were Beta Thujone (29.75%) and Phellandrene (20.20%). In disk diffusion method the most sensitive strain to the essential oil and the extracts was S. typhimurium and E.coli O157:H7. MICs of Afsantine essential oil against S. aureus and L. monocytogenes were estimated 3000 ppm. The methanolic extract showed antimicrobial activity against L. monocytogenes, E.coli O157:H7, B. cereus and S. aureus were estimated 10, 10, 8 and 4 mg ml-1, respectively. Conclusion: The results of this study revealed that the essential oil and methanlic extract of Afsantine have greater antimicrobial effects on given strains and might be used as a natural preservative in food system.